Assessment of sustainability competencies: a literature review and pathways for future research and practice - Gisela Cebriań; Jordi Segalas̀; Aǹgels Hernańdez (The Central European Review of Economics and Management (CEREM), 2019)
Aim: This paper aims at reviewing existing theoretical frameworks in sustainability competencies and identifying suitable evaluation strategies and instruments.Design / Research methods: To gain a comprehensive view of the evaluation and assessment processes of sustainability competencies a systematic literature review was conducted using a set of keywords. After a refining phase and selection of articles centred in evaluation processes a final sample of 43 articles was analysed.~~Conclusions / findings: Little evidence exists on the development, outcomes and impact that courses introducing students to sustainability competencies have. Further empirical research is needed on the development and implementation of assessment tools for sustainability competencies.Originality / value of the article: this paper outlines the state of the art of evaluation and assessment tools for sustainability competencies in higher education and suggests pathways for further research and practice based on a literature review.
Keywords: 330; sustainability competencies; sustainability; higher education; assessment; evaluation